Transcriptional analyses of the Bacillus licheniformis penP gene. - McLaughlin, J R (1982)
We report the promoter structure of the Bacillus licheniformis 749/C penicillinase (penP) gene. The transcript encoding the penicillinase gene was identified by in vitro run-off transcription using both E. coli RNA polymerase and B. subtilis RNA polymerase. Utilization of this promoter in linearized DNA by the B. subtilis RNA polymerase showed extreme sensitivity to ionic strength. The 5' sequence of the penP mRNA was determined using enzymatic sequencing (1). Holoenzymes from E. coli and B. subtilis (E sigma 55) initiate penP RNA synthesis at the same site. Alignment of this RNA sequence with the reported DNA sequence of ther penP gene (2,3) revealed the "-35 region" and "Pribnow box" sequences that are recognized as 5'TTGCAT and 5'AATACT, respectively. Potential secondary structure within the promoter exists which may play a role in the expression of the penicillinase gene. The location of the penP promoter was further confirmed by molecular cloning of a DNA fragment containing the expected promoter sequence into a promoter-fishing vector useful for monitoring promoter activities in both E. coli and B. subtilis.